Influence of the Dynamically Disordered N-Terminal Tail Domain on the Amyloid Core Structure of Human Y145Stop Prion Protein Fibrils - Qi, Zhe; Surewicz, Krystyna; Surewicz, Witold K.; Jaroniec, Christopher P. (Frontiers in Molecular Biosciences, 2022)
The Y145Stop mutant of human prion protein (huPrP23-144) is associated with a familial prionopathy and provides a convenient in vitro model for investigating amyloid strains and cross-seeding barriers. huPrP23-144 fibrils feature a compact and relatively rigid parallel in-register β-sheet amyloid core spanning ∼30 C-terminal amino acid residues (∼112–141) and a large ∼90-residue dynamically disordered N-terminal tail domain. Here, we systematically evaluate the influence of this dynamic domain on the structure adopted by the huPrP23-144 amyloid core region, by investigating using magic-angle spinning solid-state nuclear magnetic resonance (NMR) spectroscopy a series of fibril samples formed by huPrP23-144 variants corresponding to deletions of large segments of the N-terminal tail. We find that deletion of the bulk of the N-terminal tail, up to residue 98, yields amyloid fibrils with native-like huPrP23-144 core structure. Interestingly, deletion of additional flexible residues in the stretch 99–106 located outside of the amyloid core yields shorter heterogenous fibrils with fingerprint NMR spectra that are clearly distinct from those for full-length huPrP23-144, suggestive of the onset of perturbations to the native structure and degree of molecular ordering for the core residues. For the deletion variant missing residues 99–106 we show that native huPrP23-144 core structure can be “restored” by seeding the fibril growth with preformed full-length huPrP23-144 fibrils.